COMPARISON OF METACOGNITIVE AWARENESS OF MEDICAL STUDENTS DURING TWO YEARS FOLLOW UP - Tatić, Mihailo B; Nešović, Pavle; Simonović, Maja M (Medicinski podmladak, 2019)
Introduction: Metacognition is “thinking about thinking“. Metacognitive skills include planning the way to approach tasks, finding the flaws in specific strategy, monitoring comprehension or evaluating the end result of the learning process. High level of metacognitive awareness allows the person to reach the right conclusion and, therefore, ensures efficient and reliable work.Aim: The aim of the research is to identify and evaluate the metacognitive strategies used by the third year medical students and compare them with the results of the testing performed with the same generation of students during their first and second years of study.Material and methods: We compared the results of metacognitive awareness of the same generation of the medical students tested in the first, second and third year of training at the Faculty of Medicine, University of Niš. The procedure included 40 students in the first, second and third year (each) at the Faculty of Medicine, with no gender/age restrictions. The instrument used was the “Metacognitive Awareness Inventory”. The instrument consists out of 52 questions and two possible answers: true/false. The questions are grouped into 8 domains: declarative knowledge, procedural knowledge, conditional knowledge, planning, information management strategies, debugging strategies, comprehension monitoring and evaluation. We compared the average number of positive responses by the group.Results: Comparison of third and second year students showed a significant difference in the following domains: information management strategies (8 vs. 8.575), debugging strategies (4.25 vs. 4.575) and evaluation (3.725 vs. 4.325). First year students have outperformed the third year students in seven of eight tested domains, with the exception of procedural knowledge. Conclusion: Metacognitive awareness of medical students is changing during the studying period. We believe that pointing out the strategies for learning and mastering materials before and during the studies should have positive effects on the students.